Implementation of an SoC-Dependent Four-Stage Constant Current Charger for Li-Ion Batteries Based on a PSO Algorithm - Lee, Chien-Hsing; Lin, Kuei-You; Jiang, Joe-Air (IEEE transactions on aerospace and electronic systems, 2024)
This study designs a four-stage constant current (4SCC) charger in which the optimal charge pattern (OCP) adopted at each stage during the charging process varies according to the battery's current state of charge (SoC) instead of being OCP invariant. The particle swarm optimization algorithm is applied to search for the OCP value, and a battery equivalent circuit model is employed to estimate the SoC. The experimental results demonstrate that this 4SCC charging strategy with its SoC-dependent charging current profile can successfully charge batteries with different initial SoCs. Regardless of the initial SoC, adjusting the OCP value during 4SCC charging yielded shorter charging times as opposed to not adjusting the OCP value.